2020
DOI: 10.1016/j.ijheatmasstransfer.2020.119395
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer in-plane graphene/hexagonal boron nitride heterostructures: Insights into the interfacial thermal transport properties

Abstract: Combining both vertical and in-plane two-dimensional (2D) heterostructures opens up the possibility to create an unprecedented architecture using 2D atomic layer building blocks. The thermal transport properties of such mixed heterostructures, critical to various applications in nanoelectronics, however, have not been thoroughly explored. Herein, we construct two configurations of multilayer in-plane graphene/hexagonal boron nitride (Gr/h-BN) heterostructures (i.e. mixed heterostructures) via weak van der Waal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 59 publications
(32 reference statements)
3
58
0
1
Order By: Relevance
“…This is reasonable because the vibration frequency is roughly proportional to b K / m [23]. As the bond strength increased, the first peak of VDOS in the SAM no longer changed until the value of K was up to 30 To quantify the VDOS match between PEG and SAM, the overlap factor S [38] was defined as follows: To quantify the VDOS match between PEG and SAM, the overlap factor S [38] was defined as follows:…”
Section: Bond Strength Effect Of Sam On Total Rmentioning
confidence: 99%
“…This is reasonable because the vibration frequency is roughly proportional to b K / m [23]. As the bond strength increased, the first peak of VDOS in the SAM no longer changed until the value of K was up to 30 To quantify the VDOS match between PEG and SAM, the overlap factor S [38] was defined as follows: To quantify the VDOS match between PEG and SAM, the overlap factor S [38] was defined as follows:…”
Section: Bond Strength Effect Of Sam On Total Rmentioning
confidence: 99%
“…To better explain the cloaking phenomenon, we calculated the mode participation rate (MPR) [ 44 , 45 ]: where N represents the total number of atoms in the calculated domain, and according to Equation (7), PDOS i ( ω ) is the local density of states.…”
Section: Model and Methodologymentioning
confidence: 99%
“…More recently, (Ni et al, 2019) reported the dependence of thermal conductivity on interface composition diffusion in graphene/h-BN in-plane heterostructures, and demonstrated that the system's thermal conductivity is closely related to the interface composition diffusion length because of the Anderson localization of phonons. (Liang et al, 2020) found that the ITC decreases with the increase of layer number n and saturates at n 3 in multilayer in-plane graphen/h-BN heterostructures. Even so, the asymptotic value still surpasses that in monolayer heterostructures.…”
Section: Thermal Transport In 2d Heterostructuresmentioning
confidence: 96%